Analisis Naratif dalam Membangun Kepercayaan Diri Perempuan dalam Film Imperfect : Karier, Cinta & Timbangan - Retpitasari, Ellyda; Arum Permana, Silvia; Nadhiroh, Difa'un (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2024)
Building self-confidence in the midst of body shaming or physical abuse in the name of a joke without thinking about someone's feelings. Without realizing it is a form of physical humiliation. The concept of confidence in the movie Imperfect by accepting conditions and being yourself without listening to what others say. The purpose of this research is to find out how a woman builds self-confidence in the midst of society's unreasonable beauty standards. The method used in this research is the skinative method. This research uses narrative analysis with social construction theory. Researchers obtained data from literature studies both through articles, journals, books and the internet. This movie describes the self-confidence race that grows in Rara. Researchers found scenes of insecurity in the process of self-acceptance. There are 11 scenes with two sub-materials found by researchers, starting with Rara, who is not confident in herself to Rara's self-acceptance process because of being grateful for whatever her body condition is.